EFFECTS OF CALCIUM HYDROGEN PHOSPHATE ON LEAD UPTAKE BY COWPEA (VIGNA UNGUICULATA) (FUDMA JOURNAL OF SCIENCES, 2020)
The effects of calcium hydrogen phosphate on lead (Pb) uptake by cowpea (Vigna unguiculata) were investigated in a growth chamber experiment coupled with atomic absorption spectrophotometry (AAS) and colorimetry analyses. Cowpea seeds were planted and harvested in soil samples treated with Pb+2 added as lead nitrate at the rates of 0, 1000 and 3000 mg/kg followed by calcium hydrogen phosphate (CaHPO4) at 0, 10, 50 and 250 mg/kg. Increases in shoot yield brought about by phosphate fertilization were observed to oppress the shoot lead concentration as a result of growth dilution, where the actual amount of lead in shoots was unaffected by phosphate treatment. This work revealed that there is no substantial effect on lead uptake by cowpea, as a result of phosphate fertilization. Therefore, phosphate fertilization is a good means of cowpea production with minimal lead uptake and hence safe for human consumption
Keywords: Cowpea, growth chamber, calcium hydrogen phosphate, fertilization, lead